Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Prove that the group $G$ with generators $x,y,z$ and relations $z^y=z^2$, $x^z=x^2$, $y^x=y^2$ has order $1$.

This is a problem on Page 56 of Derek J.S. Robinson's A Course in the Theory of Groups (GTM 80). I think $z^y$ means the result of $y$ acting on $z$, and may be defined as $y^{-1}zy$.

Suppose that $F$ is a free group generated by $x,y,z$. The epimorphism $\pi: F \rightarrow G$ has its kernel $K$ generated by $z^yz^{-2}$, $x^zx^{-2}$, $y^xy^{-2}$. How to prove $K=F$? Or, how to prove $x,y,z \in K$? I've tried but didn't find the right way.

Thank you very much.

share|cite|improve this question
Yes: if $a$ and $b$ are elements of the group, then $a^b = b^{-1}ab$. For this kind of problem, you usually want to manipulate the relations given to conclude that $x=y=z=1$, rather than trying to work with $K$ and attempting to show that $K=F$ (it really amounts to the same thing, since showing $x=1$ amounts to showing $x\in K$, etc; it's just easier to manipulate the identities). – Arturo Magidin Aug 9 '11 at 4:02
@Arturo Magidin: I see. I'll make attempts in this direction. Thank you very much. – ShinyaSakai Aug 10 '11 at 14:47
up vote 3 down vote accepted

EDIT: I changed the steps to be somewhat simpler.

Since this is tagged homework, I will only give hints (I hope!).

  1. Look at $z^{yx}$, and write it in two fairly different ways; use the equality between these two words to write $x$ as a word in $y$ and $z$.

  2. Now look at $y^x$, and write it in two different ways; use the equality between these two words to show $x$ is a power of $z$.

  3. Use the fact $x$ is a power of $z$ to write $z^x$ in two different ways, and show $x$ is trivial; conclude your group is trivial.

share|cite|improve this answer
Thank you very much for the hint. I tagged it homework because I am still a beginner in group theory. But I am sorry I still have difficulty solving this. From $z^{yx}=(z^y)^x=(z^2)^x=x^{-1}z^2x$, and $z^{yx}=(y^{-1}zy)^x=(y^{-1})^xz^xy^x=(x^{-1}y^{-1}x)(x^{-1}zx)y^2=x^{-1}y^{-1}z‌​xy^2$, I see that $z^2x=y^{-1}zxy^2$. As $z^2=y^{-1}zy$, $x=y^{-1}xy^2$. Then how can I write $x$ in $y$ and $z$? Many Thanks. – ShinyaSakai Aug 10 '11 at 14:41
From the relations given for the group, derive the further relations $z^x=zx^{-1}$, $x^y=xy^{-1}$, $y^z=yz^{-1}$. – user641 Aug 10 '11 at 16:16
Thus $z^{yx}=z^{2x}=z(x^{-1}z)x^{-1}=z(zx^{-2})x^{-1}=z^2x^{-3}$. – user641 Aug 10 '11 at 16:17
We also have $z^{yx}=(x^{-1}y^{-1})z(yx)=(y^{-2}x^{-1})z(xy^2)=y^{-2}(zx^{-1})y^2=z^4(y^{-2}x‌​^{-1}y^2)=z^4y^2x^{-1}$. – user641 Aug 10 '11 at 16:28
So $z^2x^{-3}=z^4y^2x^{-1}$, or $x^2=y^{-2}z^{-2}$, and conjugating both by $z^{-1}$ gives $x=zy^{-2}z^{-3}=z^{-11}y^{-2}$. – user641 Aug 10 '11 at 16:30

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.